LINGKUNGAN KERJA, BUDAYA ORGANISASI, DISIPLIN KERJA DAN KINERJA KARYAWAN - Ayun Febriana; Susilowati, Heni (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
The purpose of this study was to determine how the influence of the work environment, organizational culture, and work discipline on employee performance at PT Cartini Lingerie Indonesia unit 2 Klaten. The research population consisted of 289 people was taken using a random sampling technique of 163 people. Multiple linear regression was used in this study to manage SPSS version 25 data. The study findings show that the work environment, corporate culture, and work discipline all have an impact on employee performance, either separately or together at PT Cartini Lingerie Indonesia Unit 2 in Klaten. The results of the R adjustment coefficient is 78% indicate that the work environment, organizational culture, and work discipline have an effect on employee performance, while the remaining 22% is influenced by other factors not examined such as motivation, work placement leadership, and others.